Unusual Painful Muscle Spasm in a Dialysis-Dependent Patient with Progressive Cervical Kyphosis - Daisuke Tsunoda; Yoichi Iizuka; Tokue Mieda; Haku Iizuka; Hirotaka Chikuda (Case Reports in Orthopedics)
We herein report a case of cervical myelopathy due to destructive spondyloarthropathy (DSA) with an unusual painful muscle spasm. A 51-year-old man presented to our hospital due to numbness in the hands and progressive gait disturbance. The patient underwent laminoplasty for cervical myelopathy. One and a half years after surgery, the patient developed progressive kyphosis of the cervical spine and increasing spastisity. He also started to suffer from intractable pain associated with a muscle spasm. A blood analysis revealed marked CK elevation. The patient underwent 2-stage circumferential decompression and fusion. After the revision procedure, his symptoms improved, and his serum CK level normalized. Physicians should be alert to the possibility of pain associated with an excessive muscle spasm in cervical myelopathy patients.